Pengaruh Fasilitas dan Kualitas Pelayanan Pengguna Trans Batam terhadap Kepuasan Masyarakat Kota Batam - Melda Melda; Yudhanto Satya Adiputra; Ardi Putra (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to determine the Influence of Facilities and Service Quality of Trans Batam Users on Satisfaction of Batam City Community. The population in this study were people who use Trans Batam public transportation using nonprobability sampling, namely accidental. The criteria used as samples in this study were users who had used Trans Batam public transportation, so that the number of samples was 100 respondents. This type of research is Quantitative. Validity and reliability tests were carried out on the questionnaire. Data were analyzed using multiple linear regression analysis, including t-test, F-test and coefficient of determination. This study was conducted using SPSS version 29. The results showed that partially the variables of Facilities and Service Quality had a significant effect on Satisfaction in Batam City. The results of the F Test obtained an Fcount value of 294,306 with Ftable 3.09 identifying that the variables of Facilities and Service Quality simultaneously had a significant effect on Satisfaction in the community. Based on the coefficient of determination test, around 85.6% of the satisfaction variables in the community were influenced by the variables of Facilities and Service Quality. The remaining 14.4% is influenced by other factors not explained in this study.